The Violation of Working Constitutional Right in Ecuadorian University Professors who Arrive 70 Years Natural Age - Eduardo Vallejo Romero, Julio; María Cevallos Cedeño, Angela (International Journal of Psychosocial Rehabilitation, 2020)
The education system plays a key role in the integral development of the country, especially education at the higher level that has the task of preparing the future professionals who must promote the progress of the nation in the State of Rights that fights for justice and social equity. The work is based on the problem associated with the mandatory retirement process of teachers in the Ecuadorian higher education system. The investigation has allowed analyzing the legal aspects that motivate the violation of the right of equality of said persons, where the legal obligation of the Ecuadorian State has been considered as the guarantor of the rights endorsed in the Constitution. The legal framework governing Ecuadorian higher education and especially related to the retirement of professors and researchers who work in universities are analyzed. The objective of the work is to perform a critical analysis of the legality of what is stated in article 77 of the Career and Escalator Regulation of the professor and researcher of the Higher Education System, considering what is established in the Constitution of the Republic of Ecuador approved in referendum popular in 2008.